WR 122 - English Composition: Argumentation - OER (Public) - Jennifer Kepka (Linn-Benton Community College, 2019)
COURSE OBJECTIVES: At the completion of WR122, successful students should be able to: Analyze the rhetorical needs (the needs of their audience in relationship to the assignment) for academically-oriented writing assignments. Apply appropriate levels of critical thinking strategies (knowledge, comprehension, application, analysis, synthesis, evaluation) in their written assignments, with a focus on factual, analytical, and evaluative writing. Implement appropriate rhetorical elements and organization (introduction, thesis, development and support, definition, narration, comparison, conclusion, etc.) in their written assignments. Locate, evaluate, and integrate high-quality information and opinion appropriate for college-level informational, analytical and evaluative assignments. Craft sentences and paragraphs that communicate their ideas clearly and effectively using words, sentence patterns, and writing conventions at a college level to make their writing clear, credible, and precise.